Application of Management Control System in Nepalese Commercial Banks - Rijal, Saroj (Journal of Nepalese Business Studies, 2007)
This paper attempts to examine the application of management control system in Nepalese commercial banks. The Nepalese commercial banking sector is very competitive. The commercial banks are competing mainly in service and many of them adapting differentiation strategy. The priority of the majority of commercial banks is customer retention. Commercial banks are encouraging employees to upgrade their knowledge and skill. The working environment is also congenial in Nepalese commercial banks and the informal organization and communication system also gradually exist in some of the commercial banks of Nepal. However, the future research needs to examine the relationship between management control system and effectiveness of the commercial banks of Nepal. Journal of Nepalese Business Studies 2006/III/1 pp. 92-99